Manfaat Kesehatan Psikologi Dan Sosial Yang Dirasakan Dari kegiatan Rekreasi Study Tour Dari Perspektif Siswa, Orang Tua Dan Guru Di Sekolah Menengah Pertama Swasta X Pekanbaru - Lusiana Putri MN; Tri Krianto; Novita Rany (Jurnal Kesehatan Komunitas, 2019)
Recreation benefits for Psychological and social health. Study tour recreation is organized by private junior high school X purpose to expand knowledge culture, social and tradition. Private junior high school X applies full day school system. Duration of studying is cause the student felt bored. The purpose of this research is to know the differencence between benefits of pshycology and social health at study tour from the perspective of students, the parents and teachers. Dependent variable is pschycology and social health, independent variable is perspective of students, the parents and teachers. Kind of this research descriptive comparative to cross sectional desaign. This research is done on September 2018. The sample includes 63 person.in purposive sampling. The analyse data is univariat and bivariat (one way annova). The result is univariat, is got from the total of low category is 32 person and high category 31 person. The result of the test one way annova is got p value (0,536 and 0,568)>0,05. There is no difference between student, parents and teacher in this research but still has low benefit psychological and social health. Suggested for teacher to add outbound and game in study tour, the teachers divest the students to do anything but they are controlled, adapt the place of recreation with interest students. For health and social department collaborated to socialize important of outdoor recreation.